Flower colour and phylogeny along an altitudinal gradient in the Himalayas of Nepal. (26th November 2013) - Shrestha, Mani; Dyer, Adrian G.; Bhattarai, Prakash; Burd, Martin; Shefferson, Richard
Summary Both the phylogenetic structure and trait composition of flowering plant communities may be expected to change with altitude. In particular, floral colours are thought to vary with altitude because Hymenoptera typically decline in importance as pollinators while Diptera and Lepidoptera become more important at higher elevations. Thus, ecological filtering among elevation zones and competitive processes among co‐occurring species within zones could influence the floral chromatic cues present at low and high elevations. We collected data from 107 species of native flowering plants in the Himalaya Mountains of central Nepal over an elevation range of 900–4100 m, which includes habitat ranging from subtropical to subalpine within a relatively small geographical area. Using a phylogenetic framework, we asked whether and how flower colour diversity differed between species assemblages at lower and higher elevation, between monocots and eudicots, and between our sample from central Nepal and angiosperms from other regions of the world. There was significant phylogenetic clustering in the communities as a result of monocots, particularly orchids, which were found overwhelmingly at lower elevations. Phylogenetic signal for floral colours indicated that related species had colours that were more disparate than expected under Brownian motion evolution. Floral colours were significantly more diverse in the higher elevation subalpine zone than in the subtropical zone. However, the chromatic cues at both elevations were consistent with the hue discrimination abilities of the trichromatic hymenopteran visual system. Synthesis. Flower colour is not highly differentiated between subtropical and subalpine vegetation due to differences in the available orders of insect pollinators, or by the rate or direction of colour evolution in the lineages composing the two communities. Differences in colour diversity between zones may reflect differences in the ecologically available morphospace based on pollinator species richness and the constancy of their foraging behaviour. The chromatic signals present in Nepali species are similar to the signals found in insect‐pollinated floras of other regions of the world.